(untitled) (Nexo Revista Científica, 2023)
To account for the effects of infill walls, the Iranian Code reduces the period of the structure. As a result, filler walls in the plane of structural frames result in significant changes in the properties they possess; therefore, the resistance, stiffness, ductility, distribution of internal forces, and other characteristics of such a frame with an empty frame differ greatly. In this research using 7 far-field earthquakes, a nonlinear time history analysis was performed on reinforced concrete frames with and without masonry infill walls. The maximum relative displacements between the stories were determined. Also, to evaluate the seismic performance of structural masonry walls, the fragility curve of unreinforced masonry walls retrofitted with FRP sheet based on different scenario under the effect of earthquake loads has been investigated by the finite element method. According to the results, the presence of infill walls reduces the number of plastic hinges as well as the maximum relative displacement between the stories. Furthermore, by increasing the number of FRP sheet layers and the reinforced area of the FRP sheet to the entire wall of an unreinforced structural wall, the seismic behaviour of the wall is more effective than other reinforcement patterns and damages the wall less.